2018
DOI: 10.1017/s0265051717000298
|View full text |Cite
|
Sign up to set email alerts
|

Using life histories with sound postcards to investigate a music programme for social reconstruction in Colombia

Abstract: This article outlines the development of an appropriate research approach, including methods from diverse disciplines, for researching the Colombian state-funded social music programme Music for Reconciliation (Música para la Reconciliación). After outlining the Colombian context and the literature, a pilot with ten participants is discussed. Findings show the contributions of sound postcards as part of life histories for capturing the experiences of displaced people in a country recovering from war. Their evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Music has been widely used in psychological and therapeutic interventions to enhance physical and mental health ( Peters, 1987 ; Bunt and Pavlicevic, 2001 ). The intentional use of music to improve psychological wellbeing has been studied in many areas and with different groups of people, such as those with severe diseases ( Chirico et al, 2020 ; Li Y. et al, 2020 ), physical impairments ( Grau-Sánchez et al, 2020 ; Hart et al, 2020 ), various mental health problems ( Brancatisano et al, 2020 ; Greene et al, 2020 ), relational problems ( Dunn et al, 2019 ; Dvir et al, 2020 ; Mossler et al, 2020 ), social or integration difficulties ( Crawford, 2017 ; Henderson et al, 2017 ; Rodríguez-Sánchez et al, 2018 ), and also in interventions with different population groups such as pregnant women ( Corey et al, 2019 ; Belloeil et al, 2020 ), children (Christian Gold et al, 2004 ; Hallam, 2010 ) or older people ( Coffman, 2002 ; Creech et al, 2013 ), among others. Furthermore, for many years ( Van de Wall, 1924 ) music has been used as a tool to increase psychological wellbeing in people experiencing situations of isolation or confinement; this area of interest is currently paramount in psychological and music research ( Edri and Bensimon, 2019 ; Hjørnevik and Waage, 2019 ; Gold et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Music has been widely used in psychological and therapeutic interventions to enhance physical and mental health ( Peters, 1987 ; Bunt and Pavlicevic, 2001 ). The intentional use of music to improve psychological wellbeing has been studied in many areas and with different groups of people, such as those with severe diseases ( Chirico et al, 2020 ; Li Y. et al, 2020 ), physical impairments ( Grau-Sánchez et al, 2020 ; Hart et al, 2020 ), various mental health problems ( Brancatisano et al, 2020 ; Greene et al, 2020 ), relational problems ( Dunn et al, 2019 ; Dvir et al, 2020 ; Mossler et al, 2020 ), social or integration difficulties ( Crawford, 2017 ; Henderson et al, 2017 ; Rodríguez-Sánchez et al, 2018 ), and also in interventions with different population groups such as pregnant women ( Corey et al, 2019 ; Belloeil et al, 2020 ), children (Christian Gold et al, 2004 ; Hallam, 2010 ) or older people ( Coffman, 2002 ; Creech et al, 2013 ), among others. Furthermore, for many years ( Van de Wall, 1924 ) music has been used as a tool to increase psychological wellbeing in people experiencing situations of isolation or confinement; this area of interest is currently paramount in psychological and music research ( Edri and Bensimon, 2019 ; Hjørnevik and Waage, 2019 ; Gold et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding peace education, I found five studies that explore this concept in relation to music education (Balandina, 2010; Cabedo‐Mas et al, 2017; Marsh, 2019; Rodriguez‐Sanchez et al, 2018; Rojas, 2018). Three of these explore music peacebuilding initiatives in post‐conflict societies (Balandina, 2010; Rodriguez‐Sanchez et al, 2018; Rojas, 2018). Using applied ethnomusicology, Balandina (2010) reflected on her experiences coordinating an intercultural music ensemble, during the Youth Open Festival, a community initiative ‘based on the premise that intercultural musicking constructs new possibilities for cross‐cultural understanding and may provide a paradigm for peaceful coexistence among the various ethnic groups in one nation‐state’ (that is, North Macedonia) (p. 230).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this qualitative analysis, descriptive statistics were obtained. First, the number of times each interviewee mentioned a particular sound was tallied and grouped to show the percentages reported by all interviewees to have been or to be relevant in each of the three periods in participants’ lives: BFD, AFD and “at present.” 3 Second, the sounds and their associated feelings were categorised into three thematic categories that had emerged in a previous study (Rodríguez-Sánchez, Odena et al, 2018). Each category represented a different aspect of social fabric: networks, resources , and bonds.…”
Section: Methodsmentioning
confidence: 99%
“…It asks research participants to describe the sounds associated with particular places with the aim of capturing their perceptions of their sound environments (see Data analysis for the specific question asked). We carried out a pilot study to ensure that the sound postcard would be suitable for use with participants in the MFR programme, as they were children as well as members of a displaced population, and therefore especially vulnerable (Rodríguez-Sánchez, Odena & Cabedo-Mas, 2018). The results of the pilot study showed that the sound postcard was a valuable research tool with the potential for illuminating interviewees' narratives by revealing changes in their social fabric.…”
Section: Design and Materialsmentioning
confidence: 99%